2018
DOI: 10.1111/hepr.13048
|View full text |Cite
|
Sign up to set email alerts
|

Up‐to‐seven criteria as a useful predictor for tumor downstaging to within Milan criteria and Child–Pugh grade deterioration after initial conventional transarterial chemoembolization

Abstract: The up-to-seven criteria had prognostic value and could predict non-critical recurrence and maintenance of Child-Pugh grade in patients who underwent initial conventional TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…classified patients with intermediate‐stage HCC into subgroups based on the tumor burden with the up‐to‐seven criteria, and patients out of the up‐to‐seven criteria were presumed to respond poorly to TACE . Several studies have verified the usefulness of the up‐to‐seven criteria for the classification of patients with intermediate‐stage HCC who received TACE . The present study also found that the TTTR was significantly shorter for patients out of the up‐to‐seven criteria than that for the other patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…classified patients with intermediate‐stage HCC into subgroups based on the tumor burden with the up‐to‐seven criteria, and patients out of the up‐to‐seven criteria were presumed to respond poorly to TACE . Several studies have verified the usefulness of the up‐to‐seven criteria for the classification of patients with intermediate‐stage HCC who received TACE . The present study also found that the TTTR was significantly shorter for patients out of the up‐to‐seven criteria than that for the other patients.…”
Section: Discussionsupporting
confidence: 81%
“…32 Several studies have verified the usefulness of the up-to-seven criteria for the classification of patients with intermediate-stage HCC who received TACE. [33][34][35] The present study also found that the TTTR was significantly shorter for patients out of the up-to-seven criteria than that for the other patients. Other subgrouping risk predictors, such as tumor number alone and other scoring systems (the maximum tumor diameter plus tumor number, and tumor factors plus laboratory values), have been proposed to identify ideal candidates for TACE.…”
Section: Discussionsupporting
confidence: 75%
“…In B2 substage HCC, the early onset of TACE refractoriness is responsible for the shorter survival than that of patients with B1 substage HCC [10,31]. In another retrospective study [33], multivariate analysis revealed that beyond the up-to-seven criteria is an independent factor associated with Child-Pugh class deterioration (HR, 1.9; p=0.005). These findings are large Japanese cohorts [34,35], consistent to the OS initially treated with TACE in the present study.…”
Section: Efficacy and Safetymentioning
confidence: 98%
“…Hepatocellular carcinoma (HCC) is one of the most common causes of cancer‐related death worldwide . The survival of HCC patients depends on several prognostic factors that are either host related, such as liver function and general patient status, or tumor related . The Barcelona Clinic Liver Cancer (BCLC) classification is the most widely used classification to predict prognoses and determine treatment methods .…”
Section: Introductionmentioning
confidence: 99%
“…1 The survival of HCC patients depends on several prognostic factors that are either host related, such as liver function and general patient status, or tumor related. [2][3][4][5][6] The Barcelona Clinic Liver Cancer (BCLC) classification is the most widely used classification to predict prognoses and determine treatment methods. 7 Guidelines from the European Association for the Study of the Liver and the American Association for the Study of Liver Diseases consider patients with stage 0 (very early stage BCLC) and stage A (early stage) suitable for curative treatment.…”
Section: Introductionmentioning
confidence: 99%